ADAPTASI FASHION MUSLIMAH KONTEMPORER DI KALANGAN MAHASISWI UNIVERSITAS NEGERI SEMARANG MELALUI MEDIA SOSIAL - Ningsih, Nina Martian; Alimi, Moh Yasir (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
Muslim fashion, which is synonymous with simplicity and piety, is now undergoing a transformation into a medium for self-expression, aesthetics, and even lifestyle, especially among female college students. This study aims to understand how Muslim female students at Semarang State University (UNNES) adapt contemporary Muslim clothing through social media. The approach used is descriptive qualitative, with data collection methods in the form of in-depth interviews, observations, and digital documentation from informants' social media posts. The results of the study show that social media, especially Instagram and TikTok, play a central role in the process of adapting fashion styles. Muslim female students are not only passive consumers, but also play an active role in choosing, combining, and representing clothing that suits their aesthetic tastes, personal identity, and religious values. There is a process of negotiation between sharia values and modernity, which gives birth to new forms of Muslim clothing that are more flexible and adaptive to the context of the times. In this case, social media is not just a channel for information, but also a space for producing new meanings that change the way people think, appear, and interpret Islamic identity in everyday life